Hematotoxicity in Patients with Snake Bite - Afsheen Ishfaq , Faran Maqbool , Saima Humayun Toor , Syed Irfan Ahmed (Journal of Rawalpindi Medical College, 2014)
Background: To determine the frequency of haematoxicity in patients with snake bite. Methods: In this descriptive study patients (n=84) with history of snake bite were included. After detailed history, patients were assessed for spontaneous bleeding along with evaluation of laboratory parameters for hematotoxicity. Results: Majority (71.4%) were males. Age group maximally affected by snake bite was 21-30 years (38.1%). Hematotoxicity was seen in 69% patients, while neurotoxicity was seen in 3.3% . Deranged PT and APTT were the most frequent abnormality(81%), followed by hematuria (27.6%) and thrombocytopenia (20.7%). Spontaneous bleeding from mucocutaneous sites, hematemesis and bleeding from venepuncture site were seen in 8.6%, 8.6% and 5.2% of hematotoxic snake bites respectively. Conclusion: Snakebite is a major public health problem. Hematotoxic snake bites are potentially dangerous, and are the most common type of snake bites in our setup.